"Being‐Imitated" Strategy at Home‐Based Intervention for Young Children with Autism. Issue 1 (19th November 2012) - Sanefuji, Wakako; Ohgami, Hidehiro
ABSTRACT Previous studies have consistently shown that simply imitating children with autism will help to promote amount of gaze and to decrease distance to others. However, whether the "being‐imitated" strategy also affects the development of social cognition has not been clarified. We conducted a 2‐month researcher‐guided and home‐based intervention. Mothers were randomly assigned to two groups: One group was coached to engage the child using imitation, and the other was coached simply to respond contingently to bids. Before and after the 2‐month intervention, imitation skills, understanding the intentions of others' acts, and gaze toward mothers were measured. Two months of being‐imitated enables the children to raise the general amount of their gaze interaction. The imitation skills also were promoted. On the other hand, the development of understanding others' intentions was not observed, irrespective of condition. The increase of attention to others, which is facilitated by the accumulation of the being‐imitated experiences, can be generalized to the nonimitating person and results in the imitation of others by the child. Alternatively, the developmental linkages between the being‐imitated strategy and understanding of others' intentions should be an important research task. The present study also indicates that caretakers can play a significant role in the intervention for a child with autism.